International Collaborations in Higher Education - A Case Study of OUM Business School and HUTECH, Vietnam - Wardah Mohamad,; Liana Athirah Muhammad Zamri,; Tuan Fatma Tuan Sulaiman, (Open University Malaysia (OUM), 2017)
Governments all over the world generally recognise the important role that higher education (HE) plays in meeting the challenges borne by globalisation. Australia, Europe, Singapore, Malaysia, Saudi Arabia and Dubai have all recognised the importance of internationalisation of HE and universities are turning towards franchising due to increased financial pressure, higher autonomy and an increasingly competitive market. As part of its efforts to widen access to education, OUM has ventured overseas and is currently working with many overseas partners and collaborators. This research focuses on the OUM Business School (OUMBS) which currently offers its programmes overseas through various collaborative partners. The case in hand focuses on the international collaborative partnership between OUMBS and Ho Chi Minh University of Technology (HUTECH) and discusses the current experiences faced by the two partners. Findings from the case highlight the advantages and disadvantages of a collaborative partnership plus the lessons that could be learnt. (Abstract by authors)